Angiogenic footprints in diabetic retinopathy: opportunities for drug development. Issue 1 (2nd January 2023) - Bhatia, Shiveena; Babbar, Ritchu; Zehravi, Mehrukh; Singh, Balbir; Chandel, Parteek; Hasan, Mohammad Mehedi; Arora, Rashmi; Gill, Naresh S.; Sindhu, Rakesh K.; Ahmad, Zubair; Khan, Farhat S.; Rahman, Md. Habibur
ABSTRACT: Diabetic retinopathy is one of the withering disorders that has been making the lives of patients miserable. Arising as a result of chronic high blood sugar levels in diabetes patients, retinopathy has become a major reason causing permanent blindness, retinal detachment, vitreous humor, rage, or glaucoma among patients. Angiogenesis being the major culprit behind the development of this condition is the growth of new blood vessels from the earlier ones existing. The abnormal growth and poor development of blood vessels also lead to aggravation of the conditions, with vascular endothelial growth factor (VEGF) playing a major role in the process. Various anti-angiogenic therapies or anti-VEGF therapies are being explored for the treatment of this condition. 4 widely explored drugs being-Bevacizumab, pegaptanib sodium, ranibizumab, and aflibercept. The review article tries to summarize studies illustrating the efficacy of these drugs in the treatment of diabetic retinopathy along with some of the herbal therapeutic paradigms displaying anti-angiogenic action that is being used to treat this condition.